Effect of myrtus communis extract on serum cytokines in angiotensin dependent_x000D_ hypertensive rats - (:unkn) unknown (My University, 2020)
In angiotensin dependent hypertension, high blood pressure and elevated angiotensin 2 levels lead to inflammation by increasing the pro-inflammatory cytokine levels.Since Myrtus communis have showed anti-inflammatory acvtivity in ethnobotanical researches and experimental studies, we investigated the effect of Myrtus communisextract against inflammation in a rat model of angiotensin dependent hypertension. Wistar albino rats were divided as sham-operated control, RVH and Myrtus communisextract-treated RVH groups. Left renal arteries of the rats were implanted with silver clip. Indirect blood pressure measurement of rats was provided with tail-cuff methodbefore the surgery, 3 and 9 weeks after the surgery. Myrtus communis extract (100 mg/kg, orally) or vehicle was administered for 6 weeks. At the end of the study, serumsamples were collected to investigate tumor necrosis alpha (TNF-α), interleukin-1 beta (IL-1β) and IL-6 levels. RVH resulted in significant increases in these proinflammatorycytokine levels. In the Myrtus communis extract treatment group, this increasement was abolished. The present data demonstrated that Myrtus communis attenuatesRVH-induced inflammation.